Tree-rings of Pinus hartwegii as indicators of climatic fluctuations and the influence of ocean-atmosphere phenomena in the Transmexican Volcanic Belt - Manzanilla-Quiñones, Ulises; Aguirre-Calderón , Oscar Alberto; Villanueva-Díaz, José; Martínez-Sifuentes, Aldo Rafael; Delgado-Valerio, Patricia (Instituto de Ecología, A.C., 2021)
The present study evaluates the climatic response and the influence of ocean-atmosphere phenomena on the radial growth of Pinus hartwegii Lindl in Nevado de Colima (NEC), Nevado de Toluca (NET) and Pico de Orizaba (POR). Seventy-eight growth cores were dated, and their total ring width was measured. Dating quality and chronology generation were performed in dendrochronological programs. Response analyses between dendrochronological series and climatic variables and the Niño Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO) and Atlantic Multidecadal Oscillation (AMO) indices were performed through Bootstrap correlations. Linear models were generated, calibrated, and verified through regression analysis, with which 57% and 53% of the instrumental variability of November-May precipitation for NEC (1940-2016) and December-May for NET (1928-2016) were reconstructed. The intense drought years of 1930, 1949, 1955, 1959, 1960, 1991, 1998, and 1999 and extreme wetness of 1992 coincided with the precipitation reconstructions for NEC and NET. Maximum temperature had a significant negative effect on radial growth of P. hartwegii at the three sites. The influence of ENSO on tree growth was significant (p<0.05) only at NEC. The influence of ODP and OMA was significant at all three sites (p<0.05). The local microenvironmental conditions where P. hartwegii develops in the three study sites modify the physiological response to climate and modulate the effect of ocean-atmospheric phenomena.